Palimpsests of memory: the medieval city of Athens in modern and postmodern contexts - Albani, Jenny P. (The Historical Review/La Revue Historique, 2020)
This article addresses attitudes towards the medieval past of Athens from modern to postmodern times. Athens, a symbol of classical civilisation, had become a provincial Byzantine centre. From the proclamation of Athens in 1833 as the capital of the modern Greek state to about 1880, archaeological research in Athens focused on classical antiquities at the expense of the preservation of monuments of the Middle Ages, which was regarded as a period of decline. The historical and artistic value of Athenian medieval monuments has been acknowledged since the late nineteenth century. The international progress of Byzantine studies, the national narrative on the continuity of Greek history, the political concept of the megali idea (“Great Idea”), and contemporary state policies based on “diachrony and synergy” contributed to this significant ideological shift. Athens is, however, still renowned and admired worldwide for its classical past, with its medieval cultural heritage less highlighted.